Gandrung Sewu Festival as a Sustainable Tourism Attraction in Banyuwangi, East Java - Kanom Kanom (Sebatik, 2026)
Gandrung Sewu Festival has enriched the Banyuwangi Festival series and is recognized as part of the Karisma Event Nusantara (KEN). First held in 2012, this cultural event offers more than a traditional performance; it provides educational value for tourists through a unique and modern presentation. The festival also generates positive impacts on the local community, particularly through the active participation of Banyuwangi’s younger generation in its implementation. However, several aspects still require evaluation, both internally and externally. This study aims to formulate strategies to sustain the existence of the Gandrung Sewu Festival as a sustainable tourism attraction in Banyuwangi, East Java. The research applies a quantitative descriptive method using the Internal-External (IE) Matrix as the analytical tool. The results show that the festival’s strengths include the Gandrung dance as its core identity, strong community participation, creative annual themes, and the growth of Banyuwangi’s tourism sector. The main internal strength is its strategic location, while the key weakness is the inconsistent scheduling of the event. Externally, the greatest opportunity lies in tourism sector development, while the main threat comes from natural disasters and weather conditions. This study proposes three strategic recommendations to strengthen the festival’s sustainability. The findings are expected to serve as a reference for developing event-based sustainable tourism attractions in Indonesia.